Influência do grau de embaiamento no trasporte de sedimentos das praias ao sul do ES - Alves, Fernanda Jurka (2018)
The present dissertation had the objective to analyze the influence of the embayed level on the mobility and susceptibility to erosion, under different events, in thirteen bay beaches of the south coastline of Espírito Santo state/BR. To achieve the proposed objective, distinct and complementary methods were applied. Through field surveys, it was investigated the variability of the topographic profiles and the grain size of the sands, under different conditions of the waves’ incidence. Remotely, map patterns were applied to time series satellite images, to infer the mobility’s processes that are present in each of the beaches, to trace, as a whole, the general tendency of the beach’s system from that portion of the coastline. The morphometry’s interaction about the transportation was obtained with the evaluation of the map behavior of the beaches (rotational or inundation), at first, applying the parabolic pattern, in which the predominant waves to that region were diffracted on the promontories. Considering the direction of the entry and the different amplitude of the breaking waves that occurred during the field surveys, it was possible to determine the edentation’s index of the beaches, the type of circulation, and the tendency of existing changes of sediments. The variations in the coastline, according to the diffractions suffered by the distinct spectra of waves, allowed to infer in which cases the direction of the opening of the arches to the incidence of the waves was more significant than the level of containment of those same beaches. The mobility of the topographic profiles indicates that the beaches with lower indexes of embayed present a high volumetric variability under distinct quadrants of waves’ entries. However, because of the rotational process, and possibly of the oscillatory one, that occurs in those beaches, they keep the dynamic balance between the surfaced and submerged profiles, and they become more stable than the more confined beaches. Confined beaches have lower volumes of surfaced sediment and, therefore, lower amplitudes of the variation of their volume; however, their static balance is easily disturbed by the intensity of the incidence of waves and they start to transport sediments outside their embayed areas. Just because they are more confined, they tend to have a longer period of time to the reestablishment of the exported volume. In general, the results show that, to the south coastline of ES, the embayed have a role to the protection of the beaches, until the limit in which the incidence and amplitude of the breaking weaves make the containment of the embayed stimulates the formation of currents of return. These currents intensify the mobilization and the consequent exportation of sediments to the outside of the beach cell, making the beaches more confined, sensitive and vulnerable. Taking into account the rise of the frequency of high energy events (storms and front entries) in the coastline of Espírito Santo, and that the closing profile of the analyzed beaches are mostly outside the embayed, it is imperative that the coast management of that region considers this morphodynamical beach system as integrated.